Buddha as a God: An Empirical Assessment - Purzycki, Benjamin Grant (Method & theory in the study of religion, 2019)
For at least a century, scholars have argued about whether or not Buddha is considered a god. We treat this question empirically by conducting two ethnographic studies among residents of the Tyva Republic, one of the Buddhist republics in the Russian Federation. Using a mixed methods approach to interrogate the question, this report concludes that Buddha is, in fact, popularly represented as a punitive and moralistic supernatural agent in the republic and demographic factors co-vary with such beliefs. The paper addresses longstanding concerns and situates the results in contemporary social scientific inquiry that addresses questions of when, where, to what degree, and why he is represented as a deity.